Attitude is everything: keep probe pitch neutral during side‐fire prostate biopsy. A simulator study. (22nd June 2021) - Zhang, Zhou; Lampotang, Samsun; Yu, Yichao; Acar, Yahya A.; Wakim, Jonathan; Mei, Vincent; Ahmad, Ardalan E.; Shenot, Patrick; Lee, Jason; Perlis, Nathan; Moy, Louis; Johnson, William T.; et al.
Abstract : Objectives: To develop and validate on a simulator a learnable technique to decrease deviation of biopsied cores from the template schema during freehand, side‐fire systematic prostate biopsy (sPBx) with the goal of reducing prostate biopsy (PBx) false‐negatives, thereby facilitating earlier sampling, diagnosis and treatment of clinically significant prostate cancer. Participants and Methods: Using a PBx simulator with real‐time three‐dimensional visualization, we devised a freehand, pitch‐neutral (0°, horizontal plane), side‐fire, transrectal ultrasonography (TRUS)‐guided sPBx technique in the left lateral decubitus position. Thirty‐four trainees on four Canadian and US urology programmes learned the technique on the same simulator, which recorded deviation from the intended template location in a double‐sextant template as well as the TRUS probe pitch at the time of sampling. We defined deviation as the shortest distance in millimeters between a core centre and its intended template location, template deviation as the mean of all deviations in a template, and mastery as achieving a template deviation ≤5.0 mm. Results: All results are reported as mean ± sd . The mean absolute pitch and template deviation before learning the technique (baseline) were 8.2 ± 4.1° and 8.0 ± 2.7 mm, respectively, and after mastering the technique decreased to 4.5 ± 2.7° ( P = 0.001) and 4.5 ± 0.6 mm ( P < 0.001). Template deviation was related to mean absolute pitch ( P < 0.001) and increased by 0.5 mm on average with each 1° increase in mean absolute pitch. Participants achieved mastery after practising 3.9 ± 2.9 double‐sextant sets. There was no difference in time to perform a double‐sextant set at baseline (277 ± 102 s) and mastery (283 ± 101 s; P = 0.39). Conclusion: A pitch‐neutral side‐fire technique reduced template deviation during simulated freehand TRUS‐guided sPBx, suggesting it may also reduce PBx false‐negatives in patients in a future clinical trial. This pitch‐neutral technique can be taught and learned; the University of Florida has been teaching it to all Urology residents for the last 2 years.